Chemokine CXCL1 may serve as a potential molecular target for hepatocellular carcinoma - Han, Ke‐qi (Cancer Med, 2016)
The purpose of this study was to screen for changes in chemokine and chemokine‐related genes that are expressed in hepatocellular carcinoma (HCC) as potential markers of HCC progression. Total RNA was extracted from tumor and peritumor tissues from mice with HCC and analyzed using a PCR microarray comprising 98 genes. Changes in gene expression of threefold or more were screened and subsequently confirmed by immunohistochemical analyses and western blotting. Furthermore, whether chemokine knockdown by RNA interference (RNAi) could significantly suppress tumor growth in vivo was also evaluated. Finally, total serum samples were collected from HCC patients with HBV/cirrhosis (n = 16) or liver cirrhosis (n = 16) and from healthy controls (n = 16). The serum mRNA and protein expression levels of CXCL1 in primary liver cancer patients were detected by qRT‐PCR and western blot analysis, respectively. Several genes were up‐regulated in tumor tissues during the progression period, including CXCL1, CXCL2, CXCL3, and IL‐1β, while CXCR1 expression was down‐regulated. CBRH‐7919 cells carrying CXCL1 siRNA resulted in decreased tumor growth in nude mice. The differences in serum CXCL1 mRNA and protein levels among the HCC, hepatic sclerosis (HS), and control groups were significant (P < 0.001). The mRNA and protein levels of CXCL1 in the HCC group were up‐regulated compared with the HS group or the control group (P < 0.001). Several chemokine genes were identified that might play important roles in the tumor microenvironment of HCC. These results provide new insights into human HCC and may ultimately facilitate early HCC diagnosis and lead to the discovery of innovative therapeutic approaches for HCC.